PELAKSANAAN KEBIJAKAN INTERNET MASUK DESA DI DESA TANJUNG MEDAN KECAMATAN ROKAN 1V KOTO KABUPATEN ROKAN HULU TAHUN 2018 - Yanti, Melda; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Implementation of the internet into the village policy in the form of building a wifi tower in Tanjung Medan Village is a form of basic service by the village government to the community as a support for community life activities through the internet network, and supporting the performance of village government in the villageTanjung Medan.Regulation of the Minister of Villages, Development of Disadvantaged Areas and Transmigration of the Republic of Indonesia Number 16 of 2018 concerning Priority for the Use of Village Funds in 2019 is described in Article 5 Paragraph 2 letter (a) of procurement, construction, development and maintenance of basic infrastructure for fulfillmentthe need for basic service activities and Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems.The purpose of this study is to describe the implementation of the Village Entry Internet Policy in Tanjung Medan Village, Rokan IV Koto District, Rokan Hulu Regency in 2018. This research is a descriptive study with a qualitative approach. the location of this research was carried out in the village of Tanjung Medan. Data collection techniques used were observation, interviews, and documentation. The theory used in this research is the theory of implementation or policy implementation by Merile S.grindel The data analysis technique used is a qualitative method with an interactive model.The result of the research is that the implementation of internet policy into villages in the village of Tanjung Medan, Rokan IV Koto District, Rokan Hulu Regency in 2018 has not been implemented optimally. this is because the internet program into the village has not been able to be utilized by the village government of Tanjung Medan, such as the village website has not yet been made, some people have not used the village wifi appropriately, and public services are still carried out manually. it is caused by influencing interests, types of benefits. Degree of change to be achieved, Location of decision making, program implementer, resources used and the environment in implementing internet policy into villages in Tanjung Medan Village. Keywords: Policy Implementation, Internet Entering the Village, Village Government